2019
DOI: 10.2147/ott.s195404
|View full text |Cite
|
Sign up to set email alerts
|

<p>Long non-coding RNA homeobox A11 antisense RNA (HOXA11-AS) promotes retinoblastoma progression via sponging miR-506-3p</p>

Abstract: Background: Long non-coding RNA homeobox A11 antisense RNA (HOXA11-AS) has been reported to be involved in initiation and development of multiple cancers. However, the detailed biological roles and underlying molecular mechanism of HOXA11-AS remain unclear in retinoblastoma (RB). Herein, the goals of this study were to explore the biological function and the potential mechanism of HOXA11-AS in RB. Materials and methods: The expression of HOXA11-AS in RB tissues and cell lines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 36 publications
1
14
0
Order By: Relevance
“…i The correlation between miR-506-3p and circ_100565 expression was measured by Pearson correlation analysis. *P < 0.05, **P < 0.01, ***P < 0.001 discovered that it was also lower expressed in NSCLC, which was consistent with its expression in other cancers [16][17][18]. Besides, HMGA2, a well-known oncogene, could be targeted by miR-506-3p.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…i The correlation between miR-506-3p and circ_100565 expression was measured by Pearson correlation analysis. *P < 0.05, **P < 0.01, ***P < 0.001 discovered that it was also lower expressed in NSCLC, which was consistent with its expression in other cancers [16][17][18]. Besides, HMGA2, a well-known oncogene, could be targeted by miR-506-3p.…”
Section: Discussionsupporting
confidence: 66%
“…In NSCLC, miR-217, miR-600 and miR-488-3p have also been shown to be involved in the regulation of cir-cRNAs on NSCLC progression [8,14,15]. MiR-506-3p has been shown to be under-expressed in a variety of cancers, and can act as a tumor inhibitor to participate in the regulatory process of cancer, such as prostate cancer, retinoblastoma and osteosarcoma [16][17][18]. However, its function in NSCLC is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In hepatocellular carcinoma, DLGAP1-AS1 has been confirmed to facilitate cell proliferation via the miR-486-5p/H3F3B axis (35). NR2F1-AS1 has been reported to play a role in papillary thyroid carcinoma (14), ESCC (12), endometrial cancer (15), hepatocellular carcinoma (36) and OS (16). In OS, NR2F1-AS1 has been identified to sponge miR-483-3p to upregulate FOXA1 and enhance the malignant properties of OS cells (16).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that lncRNAs have a wide range of functions in almost all physiologic processes of an organism, and they do not only regulate cell differentiation (6,7) and metabolism (8), but also participate in a variety of pathological processes, such as cancer proliferation, invasion, metastasis (9), apoptosis (10) and drug resistance (11). NR2F1-AS1, a recently discovered lncRNA, has been found to enhance esophageal squamous cell carcinoma (ESCC) progression by regulating the Hedgehog signaling pathway (12). NR2F1-AS1 has also been reported to regulate the microRNA (miR)-338-3p/cyclin D1 axis to promote thyroid cancer progression (13).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study showed that NEK6 is regulated by long non-coding RNA homeobox A11 antisense RNA (HOXA11-AS) through MiR-506-3p in retinoblastoma [154]. HOXA11-AS can decrease MiR-506-3p expression.…”
Section: Nek6mentioning
confidence: 99%